Coaching: Postmodernity’s pseudo psychology - Salomón Paredes, Alejandro Khaled (2018)
This article seeks to contribute to the understanding of the coaching phenomenon, which, for several years, has been an alternative of personal growth that presents numerous ambiguities and diffuse limits, both in its study and work object and in its methodology, as well as in the personal and professional requirements for their practice, which represents a serious danger to psychological health of those who come for help. The conditions in which coaching is produced and developed are analyzed within its socio-cultural-economic context characterized by a marked tendency towards success and happiness, with a strong facilitative orientation. Finally, it attempts to outline a psycho-hygienic culture that invites to see psychology and psychotherapy beyond psychopathology and the reductionist medical model, and oriented more towards a more integrating vision of human existence, dedicated not only to rehabilitation, but to the promotion and development of psychological functions and the promotion of a freer and more meaningful life.